Learning to be free: the importance of education in Frederick Douglass' Narrative - Stiebling, Jessica (My University, 2008)
Paper presented at the 2008 Nature, Art, Self Conference by Jessica Stiebling (University of Wisconsin-River Falls) in which she examines the importance of education to Frederick Douglass in his Narrative.
8 p.
Keywords: Abolitionists; Education; African Americans--Education; African American abolitionists; Frederick Douglass; Slaves--Education; Slaves; Douglass, Frederick, 1818-1895